Pengembangan Produksi Bersih Agroindustri Berbasis Kopi di Kecamatan Panti Kabupaten Jember - Elok Kurnia Novita Sari; Aulia Brilliantina; Agung Wahyono; Kasutjianingati Kasutjianingati (LPPM Universitas Trunojoyo Madura, 2022)
Jember coffee is well known among the public, and one of the people's coffee-producing areas to be reckoned with is Panti District, Jember Regency. Improving the welfare of the community is constrained by the many complex problems at the farmer level in maintaining these superior products. Based on this condition, this service activity is aimed at the Panti area with the Flower Farmer Group. The main problem is the lack of public knowledge in the application of environmentally sound agro-industry according to the concept of sustainable agriculture, in detail concerning several aspects, including: lack of technological innovation at the production level and no waste management for environmental sustainability. The solution provided is assistance in implementing partner agro-industry through technical innovation